LTCC를 위한 NiCuZn 페라이트계와 유전체의 이종접합의 특성 - 김남현(Nam Hyun Kim); 박현(Hyun Park); 김경남(Kyung Nam Kim) (Biuletyn Uniejowski, 2012)
The hetero junction on dielectrics and ferrite for LTCC was prepared by using NiCuZn ferrite. The shrinkage behaviour of ferrite tapes in combination with a dielectric tape was investigated. The characteristics of NiCuZn ferrite were investigated using XRD (X-ray diffractometer), Dilatometer, FE-SEM (Field emission scanning electron microscope), EDS (Energy dispersive spectrometer). NiCuZn ferrite calcined at $700^{°}C$ had a good apparent density and initial permeability of magnetic properties. The shrinkage rate of the NCZF700 ferrite and dielectric material was similar. The multilayer revealed dense, uniform morphologies with excellent interface quality. Diffusion of hetero junction such as dielectric and ferrite was not occuring at $900^{°}C$.